Exploring a novel preparation method of 1D metal organic frameworks based on supercritical CO2. Issue 16 (25th March 2015) - López-Periago, A.; Vallcorba, O.; Frontera, C.; Domingo, C.; Ayllón, J. A.
Abstract : The preparation of copper(ii ) one-dimensional MOFs using scCO2 as solvent is reported. Abstract : The preparation of copper(ii ) one-dimensional MOFs using an eco-efficient method is reported here. This method is based exclusively on using supercritical CO2 as a solvent, without the addition of any other additive or co-solvent. Neutral acetylacetonate copper complexes and two linear linkers, namely, the bidentate 4, 4′-bipyridine and 4, 4′-trimethylenedipyridine molecules, were reacted under compressed CO2 at 60 °C and 20 MPa for periods of 4 or 24 h. The success achieved in the synthesis of the different studied 1D-MOFs was related to the solubility of the reagents in supercritical CO2 . The reaction yield of the synthesized coordination polymers via the supercritical route was close to 100% because both the reactants were almost completely depleted in the performed experiments.